Kajian Feminisme dalam Novel “Cantik Itu Luka” Karya Eka Kurniawan - Katharina Woli Namang; Yeremias Bardi; Nur Sakinah (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
Feminism studies are studies that focus on the movement of women to gain freedom and determine themselves. In this beautiful novel Luka depicts the oppression of women during the Japanese colonial period. The beautiful novel Luka shows the resilience of a mixed Dutch and native woman who was detained by the Japanese army and had to be forced to work as a prostitute. The problem of this research is what is the psychological aspect of feminism analysis contained in the beautiful novel Luka by Eka Kurniawan? What is the social aspect of feminism analysis? contained in the novel "beautiful wound" by Eka Kurniawan. This research aims to find out: analysis of feminism, social aspects contained in the novel "beautiful wound" by Eka Kurniawan. The theory used by the author is mana sikana theory (2005), Ghajali, et al (1980), Ahmad Fauzi (1999). The authors used descriptive methods to conduct this research. The technique used was hermaneutic techniques. The type of research was library research. Research results (1) psychological aspects divided into character (character) thinking, taste, and emotional pressure (2) social aspects are divided into socialization process, social tasks, character (character) thinking, emotion, action, and reactions, flavors were found to be environmental factors and were influenced by age. Feelings of pressure were found to be frustration involving feelings of disappointment, sadness, sadness and suffering in each female character. Social aspects, especially the socialization process based on formal and informal education. Social tasks based on the role of wives and society. Social classes are based on lower, middle and upper class categories.